Coronary Interventions on Left Main Coronary Artery: Short-Term Outcomes of Routine Clinical Practice - I. V. Polivenok; M. S. Belimenko (Ukrainian Journal of Cardiovascular Surgery, 2019)
Background. Left main coronary artery (LM) lesions observed in 4.8–9 % of patients on coronary angiography represent a serious clinical problem with a quite aggressive revascularization strategy. Despite the growing evidence for the efficacy and safety of LM percutaneous coronary interventions (PCI), coronary bypass surgery remains the preferred method of revascularization in many hospitals.Materials and methods. The authors presented short-term results of LM PCI in 66 consecutive patients in one center.Results. LM PCI accounted for 4.9 % of the total number of percutaneous coronary interventions. 67.2 % of PCI were performed through radial access, two-stent strategies were used in 10.8%, mechanical circulatory support in 7.5%, and intracoronary imaging in 1.5 % of cases. Hospital mortality rate was 4.5%, the complications rate was 13.6 %. There were no significant differences in terms of access, technical aspects of the procedure, the number of complications and mortality rate between elective patients and patients with acute coronary syndrome.Conclusion. LM PCI may be performed routinely in the hospitals with wide experience in coronary interventions with acceptable short-term outcomes. Additional efforts are needed from the hospital administrations and professional societies to increase the use of coronary imaging in order to improve the long-term outcomes of LM PCI.